Evaluation of physicochemical, microbiological and sensorial characteristics of fermented milk beverages with buttermilk addition - De Bassi, Larissa Guilherme; Caetano Ferreira, Gessica Camila; Da Silva, Alisson Santana; Sivieri, Katia [UNESP]; Aragon-Alegro, Lina Casale; Costa, Marcela de Rezende (Wiley-Blackwell, 2012)
This study evaluated three fermented milk beverages to which had been added sugar strawberry puree post-fermentation. The base was composed of 70% of milk, with whey and buttermilk in the concentrations of 30% and 0%, 15% and 15%, and 0% and 30%, respectively. The starter culture developed well with all formulations reaching pH 4.74.9 in 180 min of fermentation. Lactic acid bacteria in the products were above 8 log cfu/mL throughout the study. The beverages presented similar pH, acidity and viscosity. Buttermilk and whey can be interesting ingredients to be added into fermented milk beverages, because the consumers liked all the products equally, which had an average acceptance score exceeding liked moderately.
Keywords: Fermentation; Functional and sensorial properties; Health-promoting products; Lactic acid bacteria; Production processing